An Effective Approach of Thinning for Morphological Features - Sharma, Kapila (International Journal of Computer Sciences and Engineering, 2025)
Thinning is a challenging and important part while involvement with any image extraction process many works have been presented in this area, many thinning algorithms though have produced good results but still there needs a lot of improvement. Most of the algorithms based on thinning an image cannot justify the connectivity of various parts of the image. This paper presents algorithm for automated thinning of linear features by maintaining the integrity of pixels in order to maintain the connectedness. The connectivity of various pixels is achieved by traversing through the pixels and considering those pixels which have maximum number of neighbors. The iterative algorithm for thinning as presented in this paper takes the image into sections and represents each section as matrix to perform number of traversals. Thinning is an essential step of data compression useful in recognition and extraction of various morphological features from topographic sheets.